THE CREATION MYTHS OF STRATFORD-UPON-ASPEN, OR, SHAKESPEARE IS QUOTING US - Winick, Stephen D. (Proverbium - Yearbook, 2018)
For years, people have claimed that Shakespeare had a prodigious vocabulary, and coined a great many common words and phrases. Modern scholarship is showing these claims to be exaggerations. One popular essay by Bernard Levin is particularly influential in claiming that whenever we utter any of 62 common phrases, we are “quoting Shakespeare.” This paper sets out to investigate these phrases, finding that fewer than a third of them are attested first in Shakespeare’s writings. It goes on to identify a few more exaggerated claims for Shakespeare as a coiner of phrases, and to explore the questions of why people tend to attribute so many phrases to him, and what consequences this has, especially regarding intellectual elitism. It concludes that most of the phrases are proverbial, that they should be considered folklore, and that they are the common heritage of all English-speakers.